2022
DOI: 10.1007/s10311-022-01481-2
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of microalgae on liquid anaerobic digestate for depollution, biofuels and cosmetics: a review

Abstract: Solid wastes from domestic, industrial and agricultural sectors cause acute economic and environmental problems. These issues can be partly solved by anaerobic digestion of wastes, yet this process is incomplete and generates abundant byproducts as digestate. Therefore, cultivating mixotrophic algae on anaerobic digestate appears as a promising solution for nutrient recovery, pollutant removal and biofuel production. Here we review mixotrophic algal cultivation on anaerobic waste digestate with focus on digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 219 publications
(205 reference statements)
1
15
0
Order By: Relevance
“…Comparing the present study with previous papers reported in Table 1 and with a recent review by Tawfick et al [38], it emerges that the present results are similar to or even better than those reached using pure cultures. Regarding the use of mixed cultures, the present results are similar to those reached by Ermis et al [39], who studied a mixed (open) microalgal consortium using the liquid fraction of the digestate from an AD plant treating the organic fraction of the municipal solid waste, cattle and chicken manure and the expired market waste and leaching water from waste collection vehicles.…”
Section: Discussionsupporting
confidence: 89%
“…Comparing the present study with previous papers reported in Table 1 and with a recent review by Tawfick et al [38], it emerges that the present results are similar to or even better than those reached using pure cultures. Regarding the use of mixed cultures, the present results are similar to those reached by Ermis et al [39], who studied a mixed (open) microalgal consortium using the liquid fraction of the digestate from an AD plant treating the organic fraction of the municipal solid waste, cattle and chicken manure and the expired market waste and leaching water from waste collection vehicles.…”
Section: Discussionsupporting
confidence: 89%
“…The method also reduces the cost of nutrient inputs. Additionally, cultivation of E. gracilis using this technique in combination with industrial nutrient wastes, anaerobic digestates of organic wastes, and exhaust CO 2 from power plants could promote a circular economy and contribute to a clean and sustainable environment 9 , 47 . Furthermore, this approach may be applied to other microalgae, providing a sustainable source of biofuels and other bioproducts.…”
Section: Discussionmentioning
confidence: 99%
“…and Scenedesmus spp. on the agricultural anaerobic digestate has been extensively discussed by Tawfik et al (2022). This approach is a promising solution for nutrient recovery and pollutant removal and achieves maximum valorization of digestate.…”
Section: Integrating Pyrolysis With Algae Cultivation For Emission Re...mentioning
confidence: 99%